Peran Kegiatan Hafalan dalam Meningkatkan Kemampuan Mengingat Anak Usia Dini: Kajian Literatur - Suhana , Mildayani (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Memory ability is one of the essential cognitive aspects that support the learning process of early childhood. Various learning strategies have been implemented to stimulate children's memory development, one of which is memorization activities. This study aims to analyze the role of memorization activities in improving memory ability in early childhood through a literature review approach. This research employed a qualitative method with a library research design by examining various scientific articles, books, and research reports related to memorization activities and memory development in early childhood. Data were collected through documentation techniques and analyzed using content analysis. The findings indicate that memorization activities play a significant role in strengthening long-term memory, improving concentration, enriching language skills, and fostering character and religious values in children. The effectiveness of memorization activities is influenced by teaching methods, learning media, environmental support, and the involvement of teachers and parents. Methods such as singing, educational games, movement and songs, and audio-visual media have been proven to enhance children's interest and ability to remember learning materials. Therefore, memorization activities can be considered an effective learning strategy to support the cognitive development of early childhood when implemented according to children's developmental characteristics.